Patient-reported outcomes and safety in patients undergoing synovial biopsy: comparison of ultrasound-guided needle biopsy, ultrasound-guided portal and forceps and arthroscopic-guided synovial biopsy techniques in five centres across Europe. Issue 2 (26th October 2018) - Just, Søren Andreas; Humby, Frances; Lindegaard, Hanne; Meric de Bellefon, Laurent; Durez, Patrick; Vieira-Sousa, Elsa; Teixeira, Rui; Stoenoiu, Maria; Werlinrud, Jens; Rosmark, Sofie; Larsen, Pia Veldt; Pratt, Arthur; et al.
Abstract : Background: We present a European multicenter study, comparing safety data and patient-reported outcomes (PRO) from patients undergoing synovial biopsy using ultrasound-guided needle biopsy (US-NB), ultrasound-guided portal and forceps (US-P&F) or arthroscopic-guided (AG) procedures. Objectives: To describe safety and PRO data on joint indices of pain, stiffness and swelling before and after biopsy, procedural discomfort, joint status compared with before biopsy and willingness to undergo a second biopsy for each technique and compare the three techniques. To evaluate the impact on PRO and safety data of corticosteroid therapy as part of the biopsy procedure and sequential biopsy procedures. Methods: Data were collected on the day of biopsy and 7–14 days postprocedure. Joint pain, swelling and stiffness indices were recorded as 0–100 mm Visual Analogue Scale; qualitative outcome variables on five-point Likert scales. Groups were compared with linear regression, adjusting for disease activity, corticosteroid therapy and prebiopsy PRO value and accounting for repeated measurements. Results: A total of 524 synovial biopsy procedures were documented (402 US-NB, 65 US-P&F and 57 AGSB). There were eight adverse events (1.5%) with no difference between biopsy methods (p=0.55). All PROs were improved 2 weeks postprocedure, and there were no differences in postbiopsy change in PROs between biopsy methods. Corticosteroid administration, whether intramuscular (n=62) or intra-articular (n=38), did not result in more adverse events (p=0.81) and was associated with reduction in postbiopsy swelling (p<0.01). Sequential biopsy procedures (n=103 patients) did not result in more adverse events (p=0.61) or worsening in PRO data. Conclusion: Overall, our results do not suggest a significant difference in safety or patient tolerability between US-NB, US-P&F and AGSB sampling. Further, corticosteroid therapy as part of the biopsy procedure and sequential biopsies is safe and well tolerated in patients.